Utilizing interactive art installation and generative quizzes to promote Kawa Daun among generation Z - Putriratu Sucihawa; Tombak Matahari; Arum Githa Putri (Deskomvis: Jurnal Ilmiah Desain Komunikasi Visual, Seni Rupa dan Media, 2025)
Kawa Daun, a traditional beverage from West Sumatra that made from roasted coffee leaf extracts, is an important cultural product but is now less popular, particularly among Generation Z. This research examines whether interactive art installations, together with generative quizzes and storytelling, can be a means to promote Kawa Daun among young generations. To address these objectives, the study focuses on these research questions: (1) How might an interactive installation be designed to engage Generation Z in spreading Kawa Daun?  (2) How can an interactive art installation use storytelling to promote Kawa Daun and connect with Generation Z's cultural and personal values? This research uses a design thinking approach to develop an installation where the intersectionality between generative quizzes and visual storytelling can communicate the cultural significance surrounding Kawa Daun. A trial was conducted for 56 participants, showing that the installation was successful in engaging the participants effectively, who were encouraged by the quizzes to know more about the cultural heritage of Kawa Daun. The conclusion is that interactive installations can efficiently bridge pre-existing cultural traditions between today's culture to ensure Kawa Daun's longevity for generations to come.